Correlation between the prevalence of E.coli O157:H7 and the physic -chemical characteristics of the soil on a dairy farm reared under field conditions in Baghdad province - Mohammed, Zuhair A. (The Iraqi Journal of Veterinary Medicine, 2022)
This study was designed to investigate the correlation of various stress factors (PH, moisture contents, temp., and soil texture) on the ability of E.coli OI57:H7 to persist on/in soil on a dairy farm reared under field conditions at the college of Agriculture /University of Bagdad. The prevalence of E. coli O157:H7 in soil samples was determined for the period January to June 2012. The surface kinetics of E.coli O157:H7 onto the soil (surface kinetics), were theoretically achieved by dividing the farm into 3 zones starting from the fens (Z1),5m, and 10 m (Z5, and Z10, respectively) from the farm in three direction (right, left and rear of the farm) . While the depth kinetics were achieved by taking soil samples from the surface (D0), and at depths of 5, and 10 cm (D5, and D10 respectively) from each zone in the three directions. Nine soil samples (200g) were collected in plastic bags for each distance of 1, 5, and 10m from the farm for each depth of zero (surface), 5 and 10 cm at weekly basis. Sub sample (100g) was made for physicochemical assays. The other subsample was analyzed for E. coli OI57:H7. In conclusion, the physico-chemical characteristics of the soil examined, PH, moisture %, sand%, and clay % showed either no consistent or weak correlations with the prevalence of E.coli O157:H7 at the dairy farm reared under field conditions. The prevalence of E. coli O157:H7 found in this study are far greater than what would likely be found on a dairy farm in other countries; this is a critically important fact considering that, under natural conditions, even a low level of contamination of E. coli O157:H7 with a low infective dose could present a human health hazard.